Unknown Caller : A Novel - Spark, Debra, 1962- (Book collections on Project MUSE., 2016)
For as long Daniella has been married to Joel, they?ve received phone calls at odd hours, and late at night. Daniella knows the caller as Liesel, Joel?s first wife, a woman whose sudden departure devastated her husband. After years of disruptive, long-distance phone calls, Liesel rings to tell Joel she?s letting Idzia, the seventeen-year-old daughter he has never met, visit for the summer. Daniella and Joel prepare for Idzia?s arrival, but when Joel goes to pick her up from the airport, Idzia isn?t there. Back at home, the phone calls suddenly stop, and Joel and Daniella become haunted by the absence of someone who was never part of their life to begin with.